Risk Factors of Fertile Age in the Inability of the Use of Long Term Contraception Method in Pekanbaru - Novita Lusiana; Ika Putri Damayanti (Institute of Computer Science (IOCS), 2021)
The population problem facing Indonesia is the large population with a low quality of life. Uncontrolled rate of population will cause a population explosion so it is necessary to disseminate information about the benefits of family planning (KB). The longterm contraceptive method (LONG TERM CONTRASEPTION) has a high level of effectiveness and can suppress the rate of population growth. The purpose of this study was to analyze the risk factors for fertile age couples in the long term failure of contraceptive methods. This research uses quantitative research with case-control study design. The population and sample in this study are couples of childbearing age in the Work Area of the Umban Sari Health Center amounting to 8055 EFAs, sampling by quota sampling. The measuring instrument used was a questionnaire. Analysis is carried out univariately and bivariately. The results of statistical tests using the chi square test are known to the independent and dependent variables namely there is a relationship between the number of children (p.value = 0.027), level of education (p.value = 0.002), knowledge (p.value = 0.0001) attitudes (p .value = 0.014), partner support (p.value = 0.01) with the unsuccessful use of long-term contraceptive methods. meanwhile the age and role of health workers have no relationship. With the use of long-term contraception methods, it is expected that health workers in the Umban Sari Health Center work area can increase health promotion of long-term contraceptive methods to EFA not only in posyandu but in the family building of each pillar. the neighbor.